The development of high-throughput assays to screen for potential anticancer and antimalarial compounds that target ADP-ribosylation factor 6 and its signalling machineries - Khan, Farrah Dilshaad (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2019)
ADP-ribosylation factors (Arfs) are small GTP-binding proteins that cycle between active GTP-bound forms and inactive GDP-bound forms. GDP/GTP cycling is regulated by large families of guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs). ArfGEFs activate Arfs by mediating the exchange of GDP for GTP, while ArfGAPs terminate Arf function by stimulating the hydrolysis of the terminal phosphate group of GTP. Arf6 is a major regulator of endocytic trafficking and reorganization of the actin cytoskeleton in eukaryotic organisms. Owing to its participation in wide range of fundamentally distinct cellular processes, Arf6 may be a drug target for cancer and malaria amongst other diseases. As with cancer cells, rapid growth and viability of eukaryotic pathogens likely places a heavy burden on their endocytic pathways and a critical reliance on Arf6 activity. A putative malarial homolog of Arf6 (PfArf6) localises to numerous puncta along the periphery of the parasite in the mature trophozoite life stage of the parasite (T. Swart, MSc dissertation). Owing to highly inefficient parasite transfection procedures and a relative shortage of well described and validated parasite organelle markers, the possible functions of PfArf6 were explored using HeLa cells as a surrogate model for parasites by fluorescence microscopy of cells transfected with GFP-tagged PfArf6. Partial co-localisation was observed with the mammalian markers HsArf6 and LC3, which suggested possible roles in Arf6-dependent endocytosis and autophagy, respectively. While these possible roles are currently under investigation in parasites, an overall long-term goal which was initiated in this study was to determine whether PfArf6 is a valid drug target. To chemically validate PfArf6 as a drug target, a potent inhibitor needs to be identified. This requires the development of assays that may be employed for high-throughput screening of compound libraries. To support this goal, a novel plate-based assay was developed using human Arf6. The assay relies on the selective binding of an Arf effector protein domain (GGA3) fused to glutathione-S-transferase (GST), to His-tagged Arf6 immobilised on a nickel-coated plate. The assay format was developed and could robustly distinguish HsArf6-GDP (inactive) from HsArf6-GTP (active). Furthermore, it could be employed to detect the deactivation of Arf6 by ArfGAP1-stimualted GTP hydrolysis, but not Arf6 activation by ARNO-stimulated GDP/GTP exchange (ARNO is an ArfGEF). The ArfGAP1 deactivation assay was chemically validated using a known ArfGAP inhibitor, QS11. An improved assay was developed that employs JIP4 as an Arf6-specific binding partner instead of GGA3. In addition to superior performance, the alternative assay format could potentially be exploited for cancer drug discovery, since Arf6-JIP4 interaction has been implicated in cancer cell invasion and metastasis. Both assays may be employed to explore alternative ArfGEFs and ArfGAPs that act on Arf6 and contribute to the advancement of cancer. In parallel experiments, where development of PfArf6 assays was the focus, several issues arose. Firstly, we could not prepare GDP- and GTP-bound forms of PfArf6 since EDTA-mediated nucleotide exchange appeared to irreversibly destabilise the protein. However, PfArf6 activation (i.e. the preparation of PfArf6-GTP) was possible when mediated by ARNO and assessed by tryptophan fluorescence kinetic assays, suggesting that PfArf6 may be expressed in GDP-bound form in E. coli. As with human Arf6, ARNO-mediated GDP/GTP exchange on PfArf6 was not detectable in the immobilised PfArf6-GGA interaction GST assay format. However, a more sensitive assay was developed which relies on the use of nickel-horseradish peroxidase to detect the binding of His-tagged PfArf6 to JIP4-GST immobilised on glutathione plates and could detect ARNO-mediated PfArf6 activation. Since we could not prepare PfArf6-GTP (that did not rely on the presence of the ArfGEF, ARNO), malarial ArfGAP deactivation studies were conducted using PfArf1 instead of PfArf6 in the GGA-GST interaction assay. Both PfArfGAP1and PfArfGAP2 stimulated GTP hydrolysis by PfArf1, but only the former was inhibited by the standard human ArfGAP inhibitor, QS11. The development of these simple, cost-effective assays can be used in the high-throughput screening of novel anticancer and antimalarial compounds that target Arf signalling machineries. In theory, the assay could be extended as a tool to identify novel inhibitors of the multitude of Arfs, ArfGEFs and ArfGAPs originating from any organism and hence has broad clinical significance.
Keywords: ADP-ribosylation; Proteins -- Metabolism; Nucleoproteins; Malaria -- Chemotherapy; Cancer -- Chemotherapy